The international standardisation of labour statistics - International Labour Office (Geneva, 1959)
The volume, to aim of that report was to make available in one volume, to officials of national statistics as well as students and research workers.
Includes bibliographical references.
aia 21/03/2019
Loans
Keywords: Labour supply - Statistics; Labour Supply - Statistics; Working class